Flavour Components of Whiskey. I. Distribution and Recovery of Compounds by Fractional Vacuum Distillation - MacNamara, K.; van Wyk, C.J.; Augustyn, O.P.H.; Rapp, A. (South African Journal of Enology and Viticulture, 2017)
A vacuum fractional distillation procedure is described for separating both the matrix components and flavour compounds of a whiskey into well-defined groups based on differences in azeotropic boiling points. The distillation was carried out at near ambient temperatures to accommodate both unaged and aged whiskies. Analytical and sensory data indicated good recovery of congeners. Individual fractions were reconstituted with ethanol and water to the original volume and strength dimensions of the whiskey. Undesirable thermal changes in the aged products were minimised by the low temperature fractionation and allowed changes in the flavour composition of whiskey due to maturation to be investigated for such unaged and aged reconstituted pairs.